Impact of the village health center project on contraceptive behaviors in rural Jordan: a quasi-experimental difference-in-differences analysis - Makiko Komasawa; Motoyuki Yuasa; Yoshihisa Shirayama; Miho Sato; Yutaka Komasawa; Malak Alouri (BMC, 2019)
Abstract Background Appropriate contraceptive use remains a major health challenge in rural Jordan. The Japan International Cooperation Agency implemented a project aimed at enhancing the capacity of village health centers (VHCs) to improve the quality and quantity of family planning (FP) services in rural Jordan in 2016-2018. Facility- and community-based approaches were integrated into the interventions. We evaluated the project's impacts on contraceptive behaviors and the effectiveness of the two approaches. Methods We used a difference-in-differences analysis based on the project baseline and endline surveys, and logistic regression analysis to assess associations between eight primary outcomes and three secondary outcomes (impacts). The unit of intervention was five target VHCs; the unit of analysis was currently married women of reproductive age (15-49 years) in five intervention and five control villages. Results Overall, 2061 married women participated; 83.8% were in need of FP. Compared with the control villages, significant effects, ranging from + 0.4% points (pp) to + 11.5 pp., were observed in the intervention villages for six primary outcomes in these categories: increasing the use of FP services at VHCs, participation in health promotion activities, and changing the sources of reproductive health information. There was a trend toward improved secondary outcomes in the intervention villages, but no significant differences were observed between the intervention and control villages regarding modern contraceptive use (mCU; + 4.3 pp), traditional contraceptive use (tCU; − 0.5 pp), and spousal agreement on contraception (+ 5.1 pp). mCU was positively associated with five primary outcomes: obtaining contraceptives at VHCs [adjusted odds ratio (AOR) 3.44, 95% confidence interval (CI) 1.26-9.40], education sessions at VHC (AOR 7.41, 95% CI 1.60-34.39), health activities in communities (AOR 7.41, 95% CI 3.28-16.78), counseling by private doctor/clinic (AOR 0.62, 95% CI 0.40-0.97), and information gained through TV (AOR 0.50, 95% CI 0.32-0.76). Spousal agreement on contraception showed similar positive trends. tCU was associated only with TV. Conclusions The project had impacts on increased mCU and husbands' perception of contraception in rural Jordan. The integration of facility- and community-based approaches may be effective in shifting from tCU to mCU in other rural areas.